Archaeological Sites as Peripheral Destinations. Exploring Big Data on Fieldtrips for an Upcoming Response to the Tourism Crisis after the Pandemic - Carlos Martínez-Hernández; Carmen Mínguez; Claudia Yubero (Heritage, 2021)
Archaeological heritage sites constitute the most recent addition to the tourism supply of Madrid, one of the most visited regions of Spain. In 2003, the Plan de Yacimientos Visitables (Plan of Archaeological Visitable Sites) was implemented, museumising 21 sites. However, the peripheral nature of these sites and the lack of personnel prevent strict control being carried out of who visits them, the practices of these visitors and how they rate the sites. This study proposes a systematic procedure to analyse the data gathered from Twitter and Flickr, in order to determine the most shared archaeological spaces in the years immediately preceding the pandemic, and to assess the perception that the visitors had of them. The information provided is useful for learning about the real weight that these sites have in leisure experiences (school trips, guided tours, recreation, etc.). Now that travel has been restricted due to the pandemic, we should ask whether Spain’s minor heritage is able to structure new proximity tourism routes. This is based on the hypothesis that, until now, these types of heritage have had a very limited role in recreational practices, but offer potential as “outdoor museums” in the present climate.